Kontribusi Pengelolaan Agroforestry Terhadap Pendapatan Petani (Studi Kasus Desa Ranaka Kecamatan Wae Ri’i Kabupaten Manggarai) - Florentina Jebaru; Wilhelmina Seran; Nixon Rammang (Wana Lestari, 2023)
This research was conducted to determine the contribution of agroforestry to farmers' income. This research was conducted in Ranaka village, WaeRi'i sub-district, Manggarai Regency " for one month, from April to May 2021. This study used survey methods and data analysis using descriptive and quantitative analysis. The data is processed using the formula for calculating farmers' income, namely: Production x Price, while income is the difference between Revenue - Costs, and Costs = Fixed Costs + Variable Costs, while the contribution of agroforestry to farmers' total income is Iaf% = (Ihr/Itot) x 100 %.The results showed that the components of the agroforestry sistem at the research site had an intercropping pattern, where in one plot of land farmers planted various types of crops, both agricultural and forestry.Research respondents on average make a living as farmers who have a low level of education with a more dominant productive age level. The agroforestry sistem applied by farmers in Ranaka Village is Agrosilviculture with mixed cropping patterns. The income received by farmers from the component of the agroforestry sistem in Ranaka Village for one year is Rp. 957,130,000 while the Non Agroforestry component is Rp. 309,600,000 per year. The total cost incurred by farmers for agroforestry management is Rp. 116,912,340, while for Non Agroforestry Rp. 870,650,000. The percentage contribution of agroforestry is very large to household income, which is 75.55% of the total farmer household income. Meanwhile, the Non Agroforestry component only contributed 24.45% of the total percentage of 100%.